Wayang Sebagai Wasilah Dakwah: Analisis Maqosid Al-Syari’ah Terhadap Seni Budaya Tradisional - Haeni Mukti; Kurniati; Fatmawati (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2026)
Wayang, as one of the cultural heritages of the Indonesian archipelago, possesses significant aesthetic, philosophical, and educational values. From the perspective of Islamic law, the existence of cultural arts such as wayang often becomes a subject of debate regarding its legal status. This study aims to examine wayang as a medium of da'wah through the approach of maqāṣid al-syarī‘ah. The research method employed is library research with a qualitative approach. The findings indicate that wayang, as a cultural product, does not have a fixed legal ruling; rather, it depends on its content, purpose, and impact. Within the framework of maqāṣid al-syarī‘ah, wayang can function as a means of preserving religion, intellect, and social values when utilized appropriately. Nevertheless, potential deviations must be anticipated, particularly when it contains elements that contradict the principle of tawḥīd. Therefore, wayang can be accepted as a contextual medium of da'wah as long as it aligns with the objectives of Islamic law.